2020
DOI: 10.1186/s12943-020-01293-4
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA NEAT1 promotes bone metastasis of prostate cancer through N6-methyladenosine

Abstract: Background N6-methyladenosine (m6A) is the most prevalent messenger RNA modification in mammalian cells. However, the disease relevant function of m6A on specific oncogenic long non-coding RNAs (ncRNAs) is not well understood. Methods We analyzed the m6A status using patients samples and bone metastatic PDXs. Through m6A high-throughput sequencing, we identified the m6A sites on NEAT1–1 in prostate bone metastatic PDXs. Mass spec assay showed inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
162
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(168 citation statements)
references
References 65 publications
5
162
0
1
Order By: Relevance
“…In previous studies, m6A modification of RNA were proved to play an important role in tumorigenesis and metastasis. Wen et al found that m6A on ncRNA NEAT1-1 plays a critical role in the pathogenesis and development of bone metastatic prostate cancer [ 8 ]. Chang et al demonstrated that overexpression of YTH domain-containing family protein 3 (YTHDF3) could induce the transcription of m6A-enriched genes to promote breast cancer metastasis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, m6A modification of RNA were proved to play an important role in tumorigenesis and metastasis. Wen et al found that m6A on ncRNA NEAT1-1 plays a critical role in the pathogenesis and development of bone metastatic prostate cancer [ 8 ]. Chang et al demonstrated that overexpression of YTH domain-containing family protein 3 (YTHDF3) could induce the transcription of m6A-enriched genes to promote breast cancer metastasis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, modification by m6A can promote the degradation of carcinogenic lncRNA XIST through the YTHDF2-dependent pathways and inhibit the proliferation and metastasis of colorectal cancer [ 145 ]. m6A modification can also stabilize LncNEAT1, which acts as a bridge between CYCLINL1 and CDK19, and promote the phosphorylation of Pol II ser2, leading to bone metastasis of prostate cancer [ 146 ]. LINC00460 directly interacts with IGF2BP2 and DHX9 to assist the recognition protein IGF2BP2 to recognize and stabilize HMGA1 mRNA, enhance the protein expression of HMGA1, and promote the proliferation and metastasis of colorectal cancer [ 147 ].…”
Section: N6-methyladenosine Can Regulate Cancer Invasion and Metastasismentioning
confidence: 99%
“…All the above analysis methods and R package were implemented by R foundation for statistical computing (2020) version 4.0.3 and software packages ggplot2 and pheatmap. MELLT3 regulates the expression of Integrin β1 (ITGB1) and a high m6A level of LncRNA NEAT1-1 promotes the bone and lung metastasis of PCa Wen et al, 2020). Du and Li et al showed that YTHDF2 performed Oncogene functions in PCa through the KDM5A/miRNA-495/YTHDF2/m6A-MOB3B axis and the downstream AKT phosphorylation of METTL3/YTHDF2/LHPP/NKX 3-1, respectively (Du et al, 2020;.…”
Section: Prostate Cancermentioning
confidence: 99%
“…In 2020, several studies have shown that m6A writer MELLT3 and VIRMA serve an oncogenic role to promotes the development and progression of PCa by Wnt pathway ( Ma et al, 2020 ) and promoting the translation of MYC ( Yuan et al, 2020 ), lncRNAs CCAT1/2 ( Barros-Silva et al, 2020 ). Other studies have proposed that MELLT3 regulates the expression of Integrin β1 (ITGB1) and a high m6A level of LncRNA NEAT1–1 promotes the bone and lung metastasis of PCa ( Li E. et al, 2020 ; Wen et al, 2020 ). Du and Li et al showed that YTHDF2 performed Oncogene functions in PCa through the KDM5A/miRNA-495/YTHDF2/m6A-MOB3B axis and the downstream AKT phosphorylation of METTL3/YTHDF2/LHPP/NKX 3-1, respectively ( Du et al, 2020 ; Li J. et al, 2020 ).…”
Section: Role Of Rna M6a Modifications In Male Genital System Tumorsmentioning
confidence: 99%